A Novel Self-Microemulsifying System for the Simultaneous Delivery and Enhanced Oral Absorption of Curcumin and Resveratrol - Jaisamut, Patcharawalai; Wiwattanawongsa, Kamonthip; Wiwattanapatapee, Ruedeekorn (Planta Medica, 2017)
The use of curcumin and resveratrol in combination has now become increasingly of interest because of their synergistic effects as therapeutic agents for various diseases, especially cancer. To overcome the poor oral bioavailability of both compounds and improve patient compliance, a novel self-microemulsifying formulation containing curcumin together with resveratrol was developed. Capryol 90, Cremophor EL, and Labrasol were selected as the oil, surfactant, and co-surfactant in the formulation, respectively, based on the solubility study of both compounds. More than 70 % and 80 % of curcumin and resveratrol, respectively, were released in 20 min. The formulation formed a fine oil in water microemulsion with droplet sizes in aqueous media of 15–20 nm. In addition, the formulation containing curcumin and resveratrol showed greater antioxidant activity than that of the formulations with individual compounds, while the cytotoxic activity against HT-29 of the co-formulation (IC50 = 18.25 µM; curcumin and resveratrol in the ratio 1 : 1) was less than the formulation with only curcumin (IC50 = 30.1 µM) and only resveratrol (IC50 = 25.4 µM). After oral administration to rabbits, the self-microemulsifying formulation containing curcumin together with resveratrol increased the total plasma concentrations of curcumin and resveratrol by 10-fold and 6-fold, respectively, compared to the unformulated combination. This study clearly demonstrated the potential use of the self-microemulsifying formulation for co-delivery, and enhanced oral absorption of poorly water-soluble natural compounds. In addition, the combination was found to produce synergistic antioxidant activity and cytotoxicity against HT-29 cells.
Keywords: self-microemulsifying drug delivery system; curcumin; resveratrol; oral absorption; co-delivery